Estimation of Stature from Percutaneous Tibial Length amongst Nepalese Students in Nobel Medical College Teaching Hospital - Kandel, Jwala; Ghimire, Samjhana (Journal of Nobel Medical College, 2021)
Background: Estimation of stature is an integral part of forensic anthropology and identification process in dead bodies. Mutilated and skeletonized body parts, which are generally received during disasters and mass casualties, carries significant burden of identification for a forensic expert. This study is aimed at estimating stature from percutaneous tibial length.Material and Methods: A cross sectional study was conducted from February 2020 to February 2021 in Nobel Medical College Teaching Hospital. 350 Nepalese medical students, 183 males and167 females, who were between 18 – 30 years, were included in the study. Their height and percutaneous tibial length was measured. Simple regression analysis was done using SPSS software version 20 to obtain a correlation between two parameters.Results: The results showed a significant correlation between the stature and percutaneous tibial length in both sexes. The regression formulae derived for calculation of stature was 104.80 + 1.81 * percutaneous tibial length(cm) for male and 93.58 + 1.91 * percutaneous tibial length(cm) for female. All the measurements were higher in males than in females.Conclusion: The study revealed a significant correlation between stature and percutaneous tibial length for both sexes in Nepalese population. Hence stature can be estimated from tibial length in both sexes which can aid in identification process and anthropological studies in Nepal.